A giant placental chorioangioma with a resultant live birth; a discussion of management options - Saša Raičević; Duško Kljakić; Filip Vukmirović; Miloš Z. Milosavljević (Clinical and Experimental Obstetrics & Gynecology)
Introduction: Chorioangiomas are benign, nontrophoblastic tumors of the placenta. Giant chorioangiomas (larger 5 cm) are infrequent and have unfavorable outcomes due to their strong association with maternal and fetal complications. We describe a case of a giant chorioangioma that had a good outcome without complications. Case report: A 27-year-old woman, primipara, with a regularly monitored pregnancy was admitted to the hospital at 37 + 5 weeks of gestation due to pain in the lower half of the abdomen, rupture of the amniotic sac and accumulation of thick, green, amniotic fluid. Ultrasonography performed at 33 weeks of gestation indicated the presence of a tumor mass 12.5 × 7.7 cm in diameter that was localized near the chorionic surface. Cardiotocography indicated variable decelerations, which necessitated an emergency cesarean section. A live, healthy, male child was born without complications via Dorfler’s cesarean section. The encapsulated tumor mass was manually removed from the uterus, and angiomatous chorioangioma of the placenta was diagnosed by pathohistological examination. Conclusion: Ultrasonographic monitoring is the choice method for the accurate diagnosis and intervention of chorioangioma, but only pathohistological examination can confirm the diagnosis. This case report demonstrates that giant placental chorioangioma may have a favorable outcome without any medical intervention.